2014
DOI: 10.1111/1440-1681.12241
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor‐4 signalling in the progression of non‐alcoholic fatty liver disease induced by high‐fat and high‐fructose diet in mice

Abstract: The aim of the present study was to investigate Toll-like receptor-4 (TLR4) signalling at different stages of non-alcoholic fatty liver disease (NAFLD) induced by a high-fat, high-fructose (HFHFr) diet in mice. Both TLR4 wild-type (WT) and mutant (TLR4(mut) ) mice were fed either standard chow (SC) or the HFHFr diet for different periods of time from 4 to 16 weeks. Pathological characteristics and function of the liver were assessed. Simple steatosis, steatohepatitis and hepatic fibrosis occurred sequentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 29 publications
2
45
0
1
Order By: Relevance
“…Fructose-induced endotoxemia activates Kupffer cells via upregulating TLR4/MyD88, which may be partially involved in the development of NAFLD [170], and subsequently trigger NF-κB activation and TNF-α overproduction [178]. Hepatic steatosis and inflammation are significantly ameliorated in TLR4-mutant mice compared with TLR4-WT mice [179]. Knock-out of lipopolysaccharide-binding protein (LBP) partially protects mice from fructose-induced NAFLD by blocking endotoxin from binding to TLR4 in liver [180].…”
Section: Indirect Dangerous Factors In Tissue and Organ Dysfunctiomentioning
confidence: 99%
“…Fructose-induced endotoxemia activates Kupffer cells via upregulating TLR4/MyD88, which may be partially involved in the development of NAFLD [170], and subsequently trigger NF-κB activation and TNF-α overproduction [178]. Hepatic steatosis and inflammation are significantly ameliorated in TLR4-mutant mice compared with TLR4-WT mice [179]. Knock-out of lipopolysaccharide-binding protein (LBP) partially protects mice from fructose-induced NAFLD by blocking endotoxin from binding to TLR4 in liver [180].…”
Section: Indirect Dangerous Factors In Tissue and Organ Dysfunctiomentioning
confidence: 99%
“…Another study reported that fructose-induced NAFLD is associated with intestinal bacterial overgrowth and increased intestinal permeability leading to an endotoxin-dependent activation of hepatic Kupffer cells and liver injury in mice [34]. Inactivation of TLR4, a receptor for LPS [34, 35], as well as administration of prebiotics and probiotics to modulate gut microbiota [36, 37] ameliorate fructose-induced hepatic steatosis in rodents.…”
Section: Nafld: Gut Barrier Endotoxemia and Dietary Factorsmentioning
confidence: 99%
“…TLR-4 is an important component of the innate immune system signaling through different ligands that recognize, among others, LPS, associated with kidney disease [7,8]. Saturated fatty acids [8], fructose [9,10], or sucrose can activate inflammatory pathways observed in obesity and kidney injury [7,8]. LPS, in turn, induces insulin resistance through the activation of the transcription factor NF-κB (nuclear factor kappa-beta) which promotes the expression of inflammatory cytokines [4], such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), which contribute to the impairment of insulin signaling, affecting kidney function [11].…”
Section: Introductionmentioning
confidence: 99%